Pengaruh Corporate Social Responsibility (CSR), Ukuran Perusahaan, Struktur Kepemilikan Institusional, Struktur Modal dan Utang terhadap Kinerja Perusahaan - Ni Kadek Siska Trisnawati; Ni Luh Putu Sandrya Dewi; Ni Luh Gde Novitasari (Jurnal Inovasi Akuntansi (JIA), 2023)
This study aims to test and obtain empirical evidence regarding the effect of corporate social responsibility (CSR), company size, ownership structure, capital structure and debt on the performance of banking companies listed on the Indonesian stock exchange in 2019-2021. The sample in this study were 25 banking companies which were determined using the purposive sampling method, namely the technique of determining the sample with certain considerations. The analytical method used to test the hypothesis is multiple linear regression analysis.The results of the study show that corporate social responsibility (CSR) has a positive effect on company performance. Meanwhile, company size, ownership structure, capital structure and debt have a negative effect on company performance.